Customer Trust, Satisfaction, and Brand Loyalty: A Study on Mixue Ice Cream & Tea in Malaysia - Najwan, Hala; Jian, Oh ZI; Goh, Wen Kai; Foo, Yong Teng; Azali, Fatimah Az Zahraa`; Gao, Xi; Tripathi, Arya; Kee, Daisy Mui Hung (AIBPM Publisher, 2024)
This study investigates customer satisfaction, trust, and loyalty within Malaysia's low-end milk tea industry, with a focus on Mixue Ice Cream & Tea. While previous research has predominantly examined how factors such as taste, perceived price, and service quality impact customer satisfaction, this study aims to bridge the gap by exploring the transition from customer loyalty to brand loyalty and its subsequent effect on brand competitiveness. Utilizing a quantitative approach, online surveys were administered to milk tea consumers across Malaysia. Our findings offer insights into brand loyalty and identify important predictors. Our study provides strategic recommendations to enhance Mixue Ice Cream & Tea's brand loyalty, thereby increasing its competitiveness in the F&B sector. Our research contributes to the existing literature by detailing how customer satisfaction and trust evolves into strong brand loyalty, highlighting the roles of customer trust and satisfaction in fostering overall customer loyalty.